Conciencia corporal y adaptación ocupacional en recicladores - Lineros Sánchez, Sofía Torcoroma; Patiño Manrique, Hilda Carolina (Revista Ciencias Básicas en Salud, 2025)
Introduction: This research was conducted in a recycling company in Pamplona, Norte de Santander. Its main objective was to determine the influence of body awareness on the occupational adaptation of recyclers in Pamplona through a quantitative study, facilitating efficiency in the performance of occupational tasks. The theoretical framework was grounded in theories specific to the discipline of occupational therapy, recognizing that adaptation depends on the individual’s capacity to adjust to environmental demands and that performance occurs as a result of the interaction between the person, their contexts, and the tasks they perform. Methodology: A quantitative, descriptive approach with a cross-sectional design was employed. The instruments applied were a sociodemographic questionnaire, the MAIA-II for body awareness, and the OPHI-II for occupational adaptation; data were processed using SPSS v23. Results: The findings revealed that high perceptual dimensions (Perception and Emotional Awareness at the 90th percentile) do not exert a protective influence on occupational adaptation. Conversely, low regulatory dimensions (Not Distracting, Attention Regulation, and Body Listening at the 40th percentile) exert a determinant negative influence on occupational identity and competence. The Emotional Awareness subscale showed a significant association with problems in Occupational Identity (OR = 4.0; 95% CI [1.02, 15.93]; p < 0.05). For Occupational Competence, two subscales presented significant associations: Emotional Awareness (OR = 28.75) and Not Distracting (OR = 0.134). In the Occupational Context, the pattern was identical to that observed in occupational competence, as the same contingencies underlie the work environment. Thus, across the three scales, odds ratios greater than 4.0 and statistical significance were observed in all cases. Conclusion: It is concluded that body awareness influences occupational adaptation in a paradoxical manner: in contexts of extreme precarity, high interoceptive perception without self-care actions intensifies the conflict between bodily needs and labor demands.